Basic sterile cell culture - Morrey, John D; Lowry, William (Utah : Taped Technologies, 1992)
Research and experiments of cell culture. Described work area, passing suspension cells, cell culture plastics, equipment and microbes.
Keywords: Cell culture; Sterilization